2011
DOI: 10.1177/1352458511415452
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin improves final visual outcome in acute optic neuritis: a randomized study

Abstract: This study provides Class I evidence that simvastatin 80 mg daily is well tolerated and possibly effective in patients with acute ON.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 36 publications
(55 reference statements)
1
53
0
1
Order By: Relevance
“…These beneficial effects were confirmed by Vollmer et al trial in 2004 [60] and in a long-term follow-up of our patients [61]. Very recently, beneficial effects of statin monotherapy were reported in patients with a first clinical episode (CIS) suggestive of MS [62][63]. A synthesis of some shared pathophysiological factors involved in MS and atherosclerosis is presented on Table 1.…”
Section: Pathophysiological Mechanismssupporting
confidence: 66%
“…These beneficial effects were confirmed by Vollmer et al trial in 2004 [60] and in a long-term follow-up of our patients [61]. Very recently, beneficial effects of statin monotherapy were reported in patients with a first clinical episode (CIS) suggestive of MS [62][63]. A synthesis of some shared pathophysiological factors involved in MS and atherosclerosis is presented on Table 1.…”
Section: Pathophysiological Mechanismssupporting
confidence: 66%
“…12,16,17,[26][27][28] When baseline characteristics of participants enrolled in RENEW were compared with those in trials of other candidate remyelinating or neuroprotective drugs, age and percentage of women were similar, mean number of days from fi rst acute optic neuritis symptom to fi rst dose was 24 days in RENEW versus 5-20 days in previous acute optic neuritis studies. 7,[22][23][24][25] A study testing erythropoietin reported shorter VEP latencies at week 16 for erythropoietin than for placebo, but the reported VEP latency was already shorter at baseline, resulting in an absence of treatment eff ect. 23 A signifi cant eff ect on VEP latency was reported for simvastatin using imputation for not detectable baseline aff ected eye values, but not for intravenous immunoglobulin or phenytoin.…”
Section: Discussionmentioning
confidence: 99%
“…23 A signifi cant eff ect on VEP latency was reported for simvastatin using imputation for not detectable baseline aff ected eye values, but not for intravenous immunoglobulin or phenytoin. 22,24,25 When comparing these trials it should be noted that RENEW is a multicentre trial and was designed to overcome the limitation of not detectable baseline aff ected eye FF-VEP latency, by using the fellow healthy eye, and to use FF-VEP latency to determine change from baseline, with rigorous procedures for performance, central reading, and standardisation of latency measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sorting through the records, nine articles [39][40][41][42][43][44][45][46][47] corresponding to eight unique trials were included in the systematic review. Five of the eight trials, with at total of 539 subjects were of statin treatment as add-on to IFNb treatment in RRMS [39][40][41][42][43] (follow-up time varying between 9 and 24 months); one trial examined statin monotherapy in SPMS [46], one trial was of statin monotherapy in CIS [47], and our research group tested statin monotherapy in acute ON patients [44]. We identified no record of studies of statins in PPMS.…”
Section: Included Studiesmentioning
confidence: 99%